Prevalencia de metalo-β-lactamasas en Pseudomonas aeruginosa resistentes a carbapenemes en un Hospital Universitario de Buenos Aires - Pagniez, Gastón (2006)
The present study was conducted to estimate the prevalence of metallo-beta-lactamases in 91 consecutive carbapenem resistant Pseudomonas aeruginosa isolates, recovered from inpatients at Hospital de Clínicas in Buenos Aires. Both, phenotypic and genotypic methods detected the presence of carbapenemases in 10 (11%) isolates, corresponding to VIM-11 in 7/10 and VIM-2 in the others. Codifying genes were all included in class 1 integrons, upstream genes coding for aminoglycoside modifying enzymes. One hundred percent sensitivity and specificity was achieved by the metallo-beta-lactamases phenotypic screening method using EDTA (1 micromol) disks in the Pseudomonas aeruginosa isolates included in this study. Sensitivity to aztreonam in carbapenem resistant isolates was suspicious of the presence of these enzymes.